Pemberdayaan Masyarakat dalam Bidang Wirausaha Gedek guna Meningkatkan Ekonomi Masyarakat di Desa Kondamara Kabupaten Sumba Timur - Iona Lisa Ndakularak; Erwin Randjawali; Irna N Sanit; Yuliana S Eko; Elsy Senides Hana Taunu; Lusianus H. Sinyo Kelen; Yubinanto Konda Meha; Apliana Umbu Ndapa; Yeni Day Hambati; Dewi Candrawati Suryani; Santri Taba Leki; Alfondro T P Kilimandu; Rolan Katanga Landa; Nikodemus Tungga Retang; Umbu Yiama Selitara; Stepanus Tamu Ama (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2022)
PkM activities carried out in the form of KKN aim to provide training on how to use social media in offering products to the gedek craftsmen in Kondamara Village, East Sumba Regency. This activity also aims to increase the knowledge and skills of gedek craftsmen in utilizing social media to make online sales. This PkM activity was carried out in July 2022 and took place at the home of one of the craftsmen in the village. Some of the methods used in this PkM activity are 1) Observation and interview methods to see the potential of the village and the constraints faced by the gedek craftsmen; 2) The lecture method to explain the meaning of social media and the benefits of social media for online marketing activities; 3) The demonstration method is used when accompanying craftsmen in creating social media accounts; 4) Discussion method to answer questions raised by the craftsmen in the training. The result of this activity is that the training activities can be carried out properly and the gedek craftsmen actively participate in these activities. The results of this activity indicate that there has been an increase in people's knowledge and skills in utilizing social media. This can be seen from the craftsman's ability to use social media to offer gedek products through social media.